The use role-play activities in improving speaking skills of first-year Chemistry-majors at Hanoi University of Industry = Sử dụng các hoạt động “đóng vai” trong việc cải thiện kỹ năng nói cho sinh viên năm thứ nhất khoa Công nghệ hóa- trường Đại học Công - Nguyễn, Thị Thúy Nga (University of Languages and International Studies, 2017)
The context of international integration and development has attached increasing importance to communication in general and oral communication in particular. Oral communication skills or speaking skills therefore have become the focus of language teaching (...)